Biomechanical Performance of Mandibular Molars with Deep Mesio-Occlusal-Distal Cavities Rehabilitated with Horizontal Posts: A 3D Finite Element Analysis - Sonali Sharma; Sindhu Ramesh; Jasmine Rayapudi (International Journal of Dentistry)
Aim. To compare and contrast by three-dimensional finite element analysis the biomechanical performance of deep mesio-occlusal-distal cavities of mandibular molars reinforced by different sizes of horizontal fiber posts. Materials and Methods. The finite element (FE) stress analysis was performed with the ANSYS, a commercial finite element method package. Based on the evidence-based scientific data and on the mechanical properties of materials, i.e., Young’s modulus and Poisson ratio, the model of a mandible and mandibular first molar was replicated. The mandibular molar models replicating the clinical scenarios were simulated, designed, and built, assuming all materials to be homogenous, isotropic, and linearly elastic as follows: Model 1 control: the model of an intact first mandibular molar. Model 2: the prepared cavity mesio-occlusal-distal is replicated by the subtraction Boolean method. The remaining thickness of dentin is 1 mm. Model 3: these were rehabilitated by three different diameters of two horizontal fiber posts. Model 3A: fiber post diameter 1 mm, Model 3B: 1.5 mm and Model 3C: 2 mm. The dimensions of the cavity, the intercuspal distance between buccal walls and lingual walls, and the distance of placement of the post from occlusal reference points were all kept constant for all three subgroups of Model 3. The cavities of Model 3 were restored with Filtek bulk-fill posterior composite. After meshing the models, loads were defined on the buccal and lingual distal cusps with a constant value of 600 N and at an angle of 45°. Results. The results of finite element analysis are expressed as stresses, i.e., tensile compressive, shear, or a combination known as von Mises stresses. The overall von Mises stresses were as follows: Model 1:154.83 Mpa; Model 2: 376.877 Mpa; Model 3A: 160.221 Mpa; Model 3B: 159.488 Mpa; Model 3C: 147.231 Mpa. Statistical analysis of the compiled data was carried out. It was seen that there was a significant difference in stress values from the intact tooth Model 1 and cavity Model 2 (p<0.05) with means values of 53.1 and 139.22, respectively. The means of all subgroups were comparable but there was a statistically significant difference between Model 3, i.e., 3A (67.74), Model 3B (60.47), Model 3C (53.70), and Model 2. Model 1 and Model 3C had comparable mean values. Conclusion. Rehabilitation of deep mesio-occlusal-distal cavities of molars with intact buccal and lingual walls with the aid of a horizontal post of any diameter has a similar stress distribution to an intact tooth. However, the biomechanical performance of a 2 mm horizontal post was exacting of the natural tooth. Horizontal posts can be included in expanding our restorative option for rehabilitating grossly mutilated teeth.